ANALISIS PROMOSI JABATAN DI SEKRETARIAT DAERAH KOTA PALU - Rustuti, Endang (Katalogis, 2015)
The purposes of this research are: (1) to assess and to analyze position promotion in Regional Secretariat of Palu; and (2) to determine the factors that support and hinder the promotion in Regional Secretariat of Palu. Type of this research is a descriptive research using nine informants that consist of the Secretary, Baperjakat, BKD, Inspectorate, and the employee who is qualified as primary data source of the research. Technique of data analysis is qualitative descriptive analysis with interactive model, the results indicate that the implementation of the promotion of civil servants in the Regional Secretariat of Palu has not been fully implemented in accordance with the general terms of promotion predetermined by Baperjakat. It is seen in terms of educational qualifications. Occasionally disciplines of employees who will be promoted is not in compliance with the vacant position. Similarly, promotion based on performance appraisal, there are employees who have a low value of DP-3 included in the promotion of employees. This means that the implementation of position promotion of employees is not in accordance with established procedures.